Uma arquitetura baseada em WBEM para o gerenciamento de um cluster de máquinas virtuais - Alexandre, Everton Batista Petró (2009)
A number of researches have been used clusters of virtual machines to emulate distributed systems. However, virtualization creates a level of indirection in the environment. In order to control a traditional environment that does not use the virtualization technology, only the reference for the physical machine is required. Nevertheless, in order to control a cluster of virtual machines, a reference is required both for the physical machine and for the virtual machine. Another difficulty found in the management of a cluster of virtual machines is related to the construction and setting up of the virtual environment. The cost related to manual management of virtual machines lifecycle and applications executing on the virtualized cluster of the environment is remarkable. Therefore, the architecture presented is intended to make available services for management applications, allowing automated construction of clusters of virtual machines, monitoring of such environments, and management of applications executed over the virtualized cluster. Additionally, the architecture decreases the complexity caused by the virtualization since, from the use of the services made available, the management applications start to reference the virtual machines only.